Modern architecture in the professional discourse: analysis of the Architectural Biennial of Quito's 1976–92 archive using bipartite networks. (21st October 2021) - Rosa Zambrano, María; Gonzalez, Mario; Medina, Ana; Acosta-Vargas, Patricia
Abstract: This article studies the contents of the Architectural Biennial of Quito's (BAQ) archive from its first edition in 1978 to its eighth in 1992, using technological tools and producing bipartite networks that make visible the inter- and intra-relationships of the archive's data through quantitative and qualitative analysis. By using these methods and means, the results firstly show how the BAQ articulated discussions of modern architecture in Ecuador, and secondly, the extent of local and international exchanges implicated in the professional scope throughout the BAQ. The study of this archive allows one to understand the most important relationships in the architectural productions and communications at the hands of BAQ as a platform for circulating ideas.